A magnetic biochar catalyst with dual active sites of Fe3C and Fe4N derived from floc: The activation mechanism for persulfate on degrading organic pollutant - Zhuo, Sheng-Nan; Sun, Hao; Wang, Zhi-Ying; Ren, Hong-Yu; Xing, De-Feng; Ren, Nan-Qi; Liu, Bing-Feng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Using floc as raw material to fabricate a magnetic biochar catalyst.•Catalyst simultaneously has dual active sites of Fe3C and Fe4N.•Fe3C enhanced the adsorption energy of persulfate on catalyst.•Fe4N promoted the adsorption and dissociation of persulfate.•The synthesis method of catalyst is innovative and worthy of development. This study, a magnetic biochar catalyst (Fe-N@MFC) with Fe3C and Fe4N was synthesized via one-step pyrolysis using waste floc as a raw material. Fe-N@MFC shows an efficient catalysis in activating peroxydisulfate (PDS) to degrade tetracycline (TC). 90.5 % of TC (5 mg/L) is removed within 60 min in the Fe-N@MFC/PDS (0.5 g/L and 1.8 mM) system with a degradation rate constant of 0.33043 min−1. Reactive oxygen species (·OH, SO4·−, 1O2, and ·O2−) and electron transfer are generated in the reaction system. ·OH and SO4·− radicals make a major contribution to TC degradation. Variation in material structure and DFT calculations prove that the existence of Fe3C and Fe4N enhances the adsorption energy of PDS and promotes the redox reaction between PDS and Fe species (Fe0 and Fe-N). Based on iron ion leaching, recycling experiment and application in real water, the Fe-N@MFC catalyst is found to exhibit promising potential. This work represents a progress compared to the traditional technology used for preparing FeNC biochar catalysts and provides significant guidance for the further development of biochar in the future.